OP2 Did proponents and opponents of the soft drinks industry levy use the news media to influence the policy debate? a qualitative discourse analysis using practical reasoning. (September 2018) - Buckton, CH; Hilton, S; Patterson, C; Katikireddi, SV; Lloyd-Williams, F; Hyseni, L; Elliott-Green, A; Capewell, S
Abstract : Background: There is growing body of evidence that indicates so-called unhealthy commodity industries (UCIs) such as alcohol and tobacco use similar tactics to resist upstream regulation and maximise profits. The media then offers UCIs a potentially important channel for direct lobbying of the public and policy-makers. In March 2016, the UK Government announced a soft drinks industry levy (SDIL) as part of its strategy to combat obesity and non-communicable diseases associated with excessive sugar consumption. The likely effectiveness of this policy has been hotly debated by stakeholders on opposing sides. The aim of this study was to use critical discourse analysis (CDA) to examine how SDIL proponents and opponents sought to influence the public and policy-makers through the news media, during a time of intense policy deliberation. Methods: We conducted a content analysis of news articles discussing the SDIL published in 11 UK newspapers between 1 April 2015 and 30 November 2016, identified through the Nexis database. Stakeholder citations were identified and imported into NVivo for qualitative coding according to a thematic typology developed and tested in a previous analysis of alcohol and tobacco industry tactics. CDA was then used to identify the presentation of circumstances, claims, counter-claims, alternative solutions, values, policy goals, means of achieving goals and consequences in order to uncover the argumentation used by opponents and proponents of the SDIL. Results: In the final sample of 491 newspaper articles, a range of 287 stakeholders were presented as citing 1761 arguments; 65% for and 35% against the SDIL. We identified three scenarios of argumentation: 1) The soft drinks industry as a public health stakeholder; 2) the SDIL as a small but important step in tackling obesity; and 3) the SDIL as a 'win-win' scenario. Our findings support the concept of a common 'playbook' of arguments used by opponents of the policy. Conversely, SDIL proponents demonstrated three sources of inconsistency: 1) change in ideological stance; 2) pursuit of academic rigour; and 3) inconsistent arguments. Discussion: Public health policy advocates engaged in media debates are faced with the direct lobbying and denialism tactics of producers and marketers of unhealthy commodities. These advocates may benefit from increasing awareness of typical UCI tactics, presenting clear and consistent objectives, and supporting arguments with quality evidence. Our CDA contributes to a growing body of literature concerning media debates about upstream legislative public health measures focussing on unhealthy commodities.